Pengaruh Pengaturan Keasaman Media Serbuk Gergaji Terhadap Pertumbuhan dan Produksi Jamur Tiram Cokelat (Pleurotus cystidiosus O.K. Miller.) - Ramza Seswati; - Nurmiati; - Periadnadi (Jurnal Biologi Universitas Andalas, 2013)
A study on the effects of sawdust acidity on the growth and production of brown oyster mushroom (Pleurotus cystidiosus O.K. Miller) was conducted from May to August 2012 in the Laboratory of Microbiology, Department of Biology, Faculty of Sciences, Andalas University, Padang. The purpose of this study was to determine the effects of acidity (pH) of sawdust media to the growth and production of the mushrooms. This study used experimental method by Completely Randomized Design (CRD) with five pH level of treatments from 4 to 8 and five replication for each pH. The results of the study showed that pH 8 gave the best growth with vegetative growth periods was 21 days, weight of the fruiting bodies was 32,60 g, and diameter of the fruiting bodies was 7,06 cm.Keywords : acidity, growth and production, Pleurotus cystidiosus, sawdust.